(untitled) (World Bulletin of Social Sciences, 2022)
The need for methodological approaches to the study of the process of paradigm development of civilization is obvious. For, knowing the principles and patterns of social reality, we acquire our own method of overcoming the crisis of our time and the paradigm of civilization. We will be able to determine where our paths lead and what is the meaning of our aspirations. Above, in the process of analyzing various definitions of civilization, we came to the conclusion that there are two main aspects in the interpretation of civilization: the first is mechanistic (the world as a mechanism) and the second is organistic (the world as an organism). The mechanistic interpretation of civilization considers society in its original form as a mechanical sum of individuals. The organic approach to the paradigm of civilization presents the life of people from the position of originality, uniqueness, pays close attention to its existential-historical aspects and rejects the unilinear development of the historical process